2004
DOI: 10.1021/jf034835f
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Selenium Uptake and Species Distribution in Lupine, Indian Mustard, and Sunflower Plants

Abstract: Selenium has been recognized as essential for all mammals; therefore, its concentration level and speciation are of great concern. Plants are one of the main sources of selenium in the diet. Thus, inorganic selenium uptake and its transformation in different species were evaluated in Indian mustard (Brassica juncea), sunflower (Helianthus annus), and white lupine (Lupinus albus). More than 1.2 g x kg(-)(1) (dry matter) of Se was found in the aerial part of Indian mustard when growing on 1 mg x L(-)(1) of Se as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 28 publications
8
48
0
Order By: Relevance
“…showed that on average, 60 to 100% of selenium in leaves and roots is selenate. In the results 360 presented by Ximenez et al (2004) in India mustard, the selenate form represents 30% in 361 roots and 90% in shoots; moreover in sunflower, selenate in leaves (35%) is similar to that inwhich is higher than in the literature, can probably be attributed to the difference in the 364 developmental stage, which was more advanced in our case. This increased metabolization of 365 selenate in fully developed mature plants could be explained by 1) increased enzymatic 366 generation (increase in the amount synthesized or in the activity rate of enzyme) and/or 2) a 367 decrease in selenate absorption at the reproductive stage involving a larger proportion of 368 selenate metabolized.…”
Section: Crop Growth Of Zea Mays 289supporting
confidence: 56%
“…showed that on average, 60 to 100% of selenium in leaves and roots is selenate. In the results 360 presented by Ximenez et al (2004) in India mustard, the selenate form represents 30% in 361 roots and 90% in shoots; moreover in sunflower, selenate in leaves (35%) is similar to that inwhich is higher than in the literature, can probably be attributed to the difference in the 364 developmental stage, which was more advanced in our case. This increased metabolization of 365 selenate in fully developed mature plants could be explained by 1) increased enzymatic 366 generation (increase in the amount synthesized or in the activity rate of enzyme) and/or 2) a 367 decrease in selenate absorption at the reproductive stage involving a larger proportion of 368 selenate metabolized.…”
Section: Crop Growth Of Zea Mays 289supporting
confidence: 56%
“…Se speciation varies with plant species and the form of Se fed to the plant [32][33][34][35][36][37]. For example, in Indian mustard (Brassica juncea), the main Se species is selenate when the plant is fed with selenate, whereas in plants fed with selenite, SeMet and SeOMet dominate [36].…”
Section: Selenium Metabolism In Plantsmentioning
confidence: 99%
“…However, in the comparing the accumulation of Se in chicory in the both experiments, it should be considered that in the 40 day treatment the Se concentration in nutrient solution decreased due to Se containing precipitate. Literature data on Se accumulation in vegetables are scarce, so for comparison of our results the studies on cultivation of vegetables in soil (Wrobel et al, 2004;Hartikainen et al, 1997) and in hydroponic system (Ximenez-Embun et al, 2004) with addition of various concentrations of selenium in the form of sodium selenate were used. The Se contents in leaves of hydroponically cultivated sunflower and lupine in selenate nutrient solution containing 5 mg Se L -1 were in the same range ( inside 100-800 μg g -1 ) as Se contents in chicory leaves after 10 days of selenium treatment in aeroponic system.…”
Section: Short Term Treatmentmentioning
confidence: 99%